2009
DOI: 10.1366/000370209788346869
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Breakdown Spectroscopy for In-Cylinder Equivalence Ratio Measurements in Laser-Ignited Natural Gas Engines

Abstract: In this contribution we present the first demonstration of simultaneous use of laser sparks for engine ignition and laser-induced breakdown spectroscopy (LIBS) measurements of in-cylinder equivalence ratios. A 1064 nm neodynium yttrium aluminum garnet (Nd:YAG) laser beam is used with an optical spark plug to ignite a single cylinder natural gas engine. The optical emission from the combustion initiating laser spark is collected through the optical spark plug and cycle-by-cycle spectra are analyzed for H(alpha)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 30 publications
5
24
0
Order By: Relevance
“…This scatter can be correlated to a number of different parameters, such as the energy stability of the laser source, the plasma's temperature and electron density, or even the interaction with the mixture. Similar investigations have been performed in the past by Ferioli et al [4,22] and Joshi et al [23], where shot-to-shot measurements were carried out in different combustion systems. Initially, Ferioli et al performed LIBS experiments in a four-cylinder engine [22] and later in a 25-mm-ID burner.…”
Section: B Uniform Methane-air Mixtures: Shot-to-shot Variationsupporting
confidence: 62%
See 1 more Smart Citation
“…This scatter can be correlated to a number of different parameters, such as the energy stability of the laser source, the plasma's temperature and electron density, or even the interaction with the mixture. Similar investigations have been performed in the past by Ferioli et al [4,22] and Joshi et al [23], where shot-to-shot measurements were carried out in different combustion systems. Initially, Ferioli et al performed LIBS experiments in a four-cylinder engine [22] and later in a 25-mm-ID burner.…”
Section: B Uniform Methane-air Mixtures: Shot-to-shot Variationsupporting
confidence: 62%
“…The relative standard deviation in their case was ranging between 2.7-3% of the mean value which was much less than the one presented during this discussion, which varied from 15-20%. Joshi et al [23] managed to both ignite and measure the equivalence ratio in a variable compression single cylinder CFR engine via the single-shot methodology. The variation of the equivalence ratio, which was calculated to be less than 10%, was related primarily to the fluctuations of the overall equivalence ratio at the spark location linked to the in-cylinder mixing.…”
Section: B Uniform Methane-air Mixtures: Shot-to-shot Variationmentioning
confidence: 99%
“…The spectral collection setup used here is an improvement over the laser ignition setup used previously by the present authors [9] and is somewhat similar to the one recently used by Joshi et al [8], have conducted incylinder LIBS measurements. In this setup, shown schematically in Fig.…”
Section: Spectral Collection Setupmentioning
confidence: 96%
“…Phuoc and White [7] advocated the use of a ratio of spectral lines corresponding to H" (656.3 nm) and O triplets (near 777 nm) and performed equivalence ratio measurements on a methane fueled laboratory-scale burner. Extending such a technique for in-cylinder measurements in a laser ignited natural gas fired engine, recently, Joshi et al [8] demonstrated an excellent correlation with equivalence ratios measured by using a UEGO sensor in the engine exhaust stream. The present investigation further extends such efforts for use with a natural gas fueled engine equipped with exhaust gas recirculation.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21] In most of these studies, the intensities of atomic lines or ratios of intensities of atomic lines have been used.…”
mentioning
confidence: 99%